Reliable multicast in wireless mesh networks based on routing quality - HU Zhi-yuan1; WANG Xiao-xiang1; ZHANG Xian2 (Tongxin xuebao, 2011)
A reliable model of multicast network was proposed and the reliability of the wireless links and nodes on the multicast routing was discussed.First,a reliable model about the relevance of wireless links and the reliability of multicast paths was established,and reliability criterion of multicast transmission was proposed.A reliable multicast network based on the combination of primary tree and multi-path tree algorithm was designed.Reliable multicast networks have multi-parallel multicast paths,so it satisfies the reliability requirement of multicast links and nodes between multicast source node and destination nodes,and provides the load sharing and hot standby functions,accordingly satisfies the multicast traffic reliability.